The Effect of 2% Lidocaine Intravenous 1,5 mg/kgBW Prior to Extubation on Cough and Sore Throat Incidence in Patients who Underwent Surgery with General Anesthesia - Ramdhani, Vicky Muhammad; , Suwarman; Redjeki, Ike Sri (Perdatin Pusat, 2015)
One of the problems that often arise in the general anesthesia is in the time of extubation of endotracheal tube. These actions can irritate the respiratory tract mucosa causing cough and sore throat. Intravenous lidocaine is one of the ways to avoid them. This study was conducted to assess the effect of 2% lidocaine intravenous 1.5 mg/kgBW before extubation to reduce the incidence of cough and sore throat in patients who underwent surgery with general anesthesia. Double blind randomized controlled trial study involved 72 patients age 18–60 years old whom underwent surgery with general anesthesia. Subjects were divided into two groups, one group using 2% lidocaine 1.5 mg/kgBW and control group using NaCl 0.9% before extubation. Data was analyzed using Chi square and Mann-Whitney test with result of p<0,05 was significant. The result showed that administration of lidocaine 1.5 mg/kgBW gave significant effects compared to 0.9% NaCl in reducing the incidence of cough with p values=0,034 and sore throat with p values=0,000 at each observation time. It can be concluded from this research that 2% lidocaine intravenous 1.5 mg/kg can reduce the incidence of cough and sore throat caused by extubation in patients who underwent surgery with general anesthesia.